Cortical–Subcortical Interactions in Hypersomnia Disorders: Mechanisms Underlying Cognitive and Behavioral Aspects of the Sleep–Wake Cycle - Larson-Prior, Linda J.; Ju, Yo-El; Galvin, James E. (Frontiers in Neurology, 2014)
Subcortical circuits mediating sleep-wake functions have been well characterized in animal models, and corroborated by more recent human studies. Disruptions in these circuits have been identified in hypersomnia disorders such as narcolepsy and Klein-Levin Syndrome, as well as in neurodegenerative disorders expressing excessive daytime sleepiness. However, the behavioral expression of sleep-wake functions is not a simple on-or-off state determined by subcortical circuits, but encompasses a complex range of behaviors determined by the interaction between cortical networks and subcortical circuits. While conceived as disorders of sleep, hypersomnia disorders are equally disorders of wake, representing a fundamental instability in neural state characterized by lapses of alertness during wake. These episodic lapses in alertness and wakefulness are also frequently seen in neurodegenerative disorders where EEG demonstrates abnormal function in cortical regions associated with cognitive fluctuations. Moreover, functional connectivity MRI shows instability of cortical networks in individuals with cognitive fluctuations. We propose that the inability to stabilize neural state due to disruptions in the sleep-wake control networks is common to the sleep and cognitive dysfunctions seen in hypersomnia and neurodegenerative disorders.